PENGARUH DOSIS PUPUK KANDANG AYAM DAN NPK (16:16:16) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KENTANG (Solanum tuberosum L.) VARIETAS GRANOLA - Yudi Yusdian; Abdul Nazar; Dian Murti Minangsih (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2022)
The aims of this research is to determine the interaction between chicken manure dose and NPK (16:16:16) and also to obtain the dose that can give the best effect on the growth and yield of potato plants (Solanum tuberosum L.) Varieties of Granola. The research was carried out on August to November 2020, in Pangkalan Kamojang, Laksana Village, Ibun District, Bandung Regency, West Java with an altitude of 1.500 m above sea level. This research used a factorial randomized block design (RBD) with 3 replications. Factor I: Dose of chicken manure (k1 = 5 tons/ha, k2 = 10 tons/ha, k3 = 15 tons/ha). Factor II: Dose of NPK 16:16:16 (n1 = 350 kg/ha, n2 = 400 kg/ha, n3 = 450 kg/ha). The results showed that there was an interaction between the dose of chicken manure and NPK (16:16:16) on the weight of tubers per plant. The best results were shown by the combination of k3n2 treatment (15 ton/ha chicken manure dose and 400 kg/ha NPK 16:16:16). Dose treatment of chicken manure gave effect on plant height, number of stems, number and weight of tubers per plant, and tuber weight per plot. Dose treatment of NPK (16:16:16) gave effect on plant height, number of stems, number and weight of tubers per plant, and tuber weight per plot. Keywords: Potato, dosage, chicken manure, NPK